2019
DOI: 10.1007/s10584-018-2357-1
|View full text |Cite
|
Sign up to set email alerts
|

Managing expectations: articulating expertise in climate services for agriculture in Belize

Abstract: A range of institutions and individuals are engaging in the provision, translation, and application of scientific climate information, with the aim of supporting agricultural decision-making in the context of climate variability and change. This article contributes to understanding political and ethical dimensions of climate services by focusing on how expertise is articulated by those who deliver anticipatory information to potential users. The article draws on interviews and observations with forecasters, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…In relation to climate issues, these individuals tend to be agronomists, cartographers, hydrologists, union leaders, activists, health agents, nurses, rural schoolteachers, technicians at municipal governments and -indeed -shamans (Arregui 2018; Kopenawa; Albert 2013). The work of professionals with such characteristics tends to be based on the translation of meanings, creative construction of pragmatic solutions and management of expectations (Haines, 2019), where the criteria for success are based on the satisfaction of the involved collectivities, and the adopted strategies seem often to lack conceptual or epistemological coherence. In this, it what resembles shamanism: the possibility of constructing improbable bridges across incoherent worlds, resulting in different people acting together, in satisfactory ways, without thinking alike.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to climate issues, these individuals tend to be agronomists, cartographers, hydrologists, union leaders, activists, health agents, nurses, rural schoolteachers, technicians at municipal governments and -indeed -shamans (Arregui 2018; Kopenawa; Albert 2013). The work of professionals with such characteristics tends to be based on the translation of meanings, creative construction of pragmatic solutions and management of expectations (Haines, 2019), where the criteria for success are based on the satisfaction of the involved collectivities, and the adopted strategies seem often to lack conceptual or epistemological coherence. In this, it what resembles shamanism: the possibility of constructing improbable bridges across incoherent worlds, resulting in different people acting together, in satisfactory ways, without thinking alike.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the world as political and contingent impinges on the view of the 'globe' , even as the latter pretends to detachment: "each view contains the seeds of the other" (Ingold, 1993: 41). Real and perceived power imbalances within and between sectors or between governments and publics complicate efforts to map and manage: for example, attempts by sugar industry researchers to collect data on multiple variables for growers' fields were not universally welcomed by farmers (Haines, 2019); projects to demarcate land use in southern Belize have encountered and created complex political-ontological struggles (Wainwright, 2008). Nonknowledge is threaded throughout these narratives -sometimes as potentially reducible epistemic uncertainty, but also as ontological indeterminacy and political critique (Mathews, 2014).…”
Section: Discussion: Political Lives Of Anticipationmentioning
confidence: 99%
“…Predicting future water resources is but one consideration: the question of what can be done about variable conditions is entangled with the capacity and values of the individual or organisation (electricity distributors worried about value for money; dam operators worried about infrastructure failure; water supply managers prioritised quality). A high-profile industrial dispute in the sugar sector during my stay demonstrated that while the timing of rains is important for the sugar harvest, political contingencies and negotiations of quotas, prices, and farmer autonomy are crucial (Haines, 2019). Anticipation as an affective state (Adams et al, 2009;Zaloom, 2009) may be experienced and addressed very differently according to how individuals and collectives are positioned and oriented in relation to environmental conditions, more-or-less shared systems of reckoning, decision-making processes, emotional engagements, and capacities to act on information.…”
Section: Reckoning Otherwisementioning
confidence: 97%
“…When the needs of all users, especially climate-vulnerable populations are represented in RCOF processes and outcomes, usability of the climate information improves. However, processes such as the RCOF inherently prioritize the knowledge of certain institutions and actors over others, potentially leaving out the needs and priorities of those most vulnerable to climate risk (Haines 2019). Engaging in interdisciplinary vulnerability assessments that frame climate vulnerability as a complex social process, and not only as a product of exposure, is an important step to ensure that RCOFs promote climate adaptation (Carr and Owusu-Daaku 2016;Gerlak and Greene 2019).…”
Section: E780mentioning
confidence: 99%